2019
DOI: 10.1088/1755-1315/292/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics, yield and quality of black pepper Ciinten variety in three agro ecological conditions

Abstract: Indonesia has long been known as one of the world major producers of black pepper. Bangka Belitung and Lampung provinces are the main black pepper production regions in Indonesia. In addition, West Java is also one of the pepper-producing regions. This research aims at observing the morphological characteristics, yield and quality of a local variety that has been grown in West Java. The observations were carried out in three agro ecological conditions Sukabumi, Purwakarta and Ciamis districts during two harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 2 publications
4
17
0
Order By: Relevance
“…The improved varieties "Panniyur-6" (clonal selection of landrace "Karimunda") and "Panniyur-7" (an open pollinated progeny of landrace "Kalluvally") of India were described as having compact spike setting (Arya et al 2003) which was similar to "Ismailia" and "Babu ndogo" in this study. Similar findings have been reported on variety "Ciinten" from Indonesia which is characterized with compact spikes and was associated to higher percentage of hermaphrodite flowers (Bermawie et al 2019). High percentage (98%) of productive bisexual flowers and berry setting percentage (91.5%) was also attributed to the very compactly arranged berries (133 berries spike −1 ) on improved variety "Panniyur-7" (Arya et al 2003).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The improved varieties "Panniyur-6" (clonal selection of landrace "Karimunda") and "Panniyur-7" (an open pollinated progeny of landrace "Kalluvally") of India were described as having compact spike setting (Arya et al 2003) which was similar to "Ismailia" and "Babu ndogo" in this study. Similar findings have been reported on variety "Ciinten" from Indonesia which is characterized with compact spikes and was associated to higher percentage of hermaphrodite flowers (Bermawie et al 2019). High percentage (98%) of productive bisexual flowers and berry setting percentage (91.5%) was also attributed to the very compactly arranged berries (133 berries spike −1 ) on improved variety "Panniyur-7" (Arya et al 2003).…”
Section: Discussionsupporting
confidence: 76%
“…Observation and recording of morphological characters/descriptors has been a typical approach for identification and description of various pepper germplasms (Hussain et al 2017b;Bermawie et al 2019;Prayoga et al 2020). Other methods include pedigree, agronomic performance, biochemical and molecular/DNA-based data (Mohammadi and Prasanna 2003;Raghavan et al 2010;Deka et al 2016).…”
mentioning
confidence: 99%
“…Campylodromous venation is which several primary veins run in prominent, recurved arches at the base, curving upward to converge at the leaf apex (Simpson 2011). The same type of leaf vein is also found in Ciinten variety (Bermawie 2019). Variations in the shape of black pepper leaves found were ovate-elliptic, ovate-lanceolate and elliptic-lanceolate ( Figure 3).…”
Section: Agro-morphological Characters Of Black Pepper In Bangka Islandsupporting
confidence: 62%
“…Based on Pusat Perlindungan Varietas Tanaman dan Perizinan Pertanian (2019), black pepper varieties in Indonesia have mostly ovate leaf lamina shape, round leaf base shape, and even type of leaf margin (Table 4). Bermawie (2019) also reported that Ciinten variety had an ovate-lanceolate leaf lamina shape, acute leaf tip, and cordate type of leaf base shape. The types of lateral branch habit observed had three types namely erect, horizontal and hanging ( Figure 6).…”
Section: Agro-morphological Characters Of Black Pepper In Bangka Islandmentioning
confidence: 90%
See 1 more Smart Citation